Incidence and determinants of spontaneous hepatitis B surface antigen seroclearance and seroconversion in hepatitis B e antigen‐negative chronic infection patients: A population‐based prospective cohort. Issue 12 (11th September 2018) - Zhu, Liguo; Zhai, Xiangjun; Wang, Qungang; Jiang, Jie; Peng, Hong; Song, Ci; Ge, Zijun; Qian, Jiao; Zhou, MingHao; Zhou, Yan; Xu, Jianfang; Liu, Hongjian; et al.
Summary: Seroclearance of hepatitis B surface antigen (HBsAg) has been widely studied; however, seroconversion of HBsAg and characteristics of viral load among hepatitis B e antigen (HBeAg)‐negative chronic infection patients after HBsAg lost is not clear. We performed a large‐scale study in a HBeAg‐negative chronic infection cohort to evaluate spontaneous HBsAg seroclearance incidence from October 2012 to April 2017 in Jiangsu province, China. We also elucidated the characteristics of HBsAg seroconversion and hepatitis B virus (HBV) DNA detectability among patients who cleared HBsAg. A total of 2997 HBeAg‐negative chronic infection patients (mean age 52.3 ± 12.9 years at baseline) were included. With 10 519 person‐years of follow‐up, 348 patients successfully spontaneously cleared HBsAg, with an incidence rate of 3.31 per 100 person‐years. Patients with HBV DNA detectable 1999 IU/mL at baseline had a lower probability of HBsAg seroclearance relative to those with undetectable HBV DNA, with a hazard ratio of 0.31 (95% CI = 0.23, 0.41). HBsAg seroconversion occurred in 37.3% of those patients who cleared HBsAg. The geometric mean of anti‐HBs among those with HBsAg conversion was 79.4 mIU/mL. Female had a higher HBsAg seroconversion rate ( P = 0.011). Among those with HBsAg seroclearance, 11.2% still had HBV DNA levels of higher than 100 IU/mL. Patients with higher HBV DNA at baseline had a higher risk of detectable HBV DNA levels even after HBsAg seroclearance ( P < 0.001). This study reveals HBsAg seroconversion rates and HBV DNA undetectability epidemiological characteristics of patients with HBsAg seroclearance and suggests that monitoring HBV DNA is needed when managing HBeAg‐negative chronic patients, even after clearing HBsAg.